2020
DOI: 10.1016/j.anaerobe.2019.102079
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of poor outcome in Clostridioides difficile infection: A multicentre external validation of the toxin B amplification cycle

Abstract: Classification of patients according to their risk of poor outcomes in Clostridioides difficile infection (CDI) would enable implementation of costly new treatment options in a subset of patients at higher risk of poor outcome. In a previous study, we found that low toxin B amplification cycle thresholds (C t ) were independently associated with poor outcome CDI. Our objective was to perform a multicentre external validation of a PCR-toxin B C t as a marker of poor outcome CDI. We carried out a multicentre stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 30 publications
(25 reference statements)
0
2
1
Order By: Relevance
“…A few other studies have identified a significant association between lower Ct values and poor outcomes, which included recurrent CDI. 13,15,16 However, all of the aforementioned studies included very few patients with recurrence, and the recurrence rates were higher than the 10% recurrence rate in our study, which may explain some of the differences. Therefore, despite some evidence that PCR Ct is able to predict disease recurrence of C. difficile, larger, prospective studies are needed to confirm its potential utility.…”
Section: Discussioncontrasting
confidence: 58%
See 1 more Smart Citation
“…A few other studies have identified a significant association between lower Ct values and poor outcomes, which included recurrent CDI. 13,15,16 However, all of the aforementioned studies included very few patients with recurrence, and the recurrence rates were higher than the 10% recurrence rate in our study, which may explain some of the differences. Therefore, despite some evidence that PCR Ct is able to predict disease recurrence of C. difficile, larger, prospective studies are needed to confirm its potential utility.…”
Section: Discussioncontrasting
confidence: 58%
“…Reigadas et al, 15 in a study involving 129 patients, found that PCR Ct was independently associated with poor-outcome CDI, with 8 of 43 poor outcomes attributed to development of severe CDI. Reigadas et al 16 performed a subsequent external validation study across 14 hospitals with 223 patients and reported similar results. However, neither study reported specific analyses regarding the association of PCR Ct with C. difficile disease severity.…”
Section: Discussionmentioning
confidence: 69%
“…� Clostridium Clostridium innocuous has recently been identified as the pathogen of antibiotic associated diarrhea in humans [31].…”
Section: Group Y2mentioning
confidence: 99%